EFFECTIVENESS OF GREEN BETEL LEAF EXTRACT (Piper betle) FOR CONTROLLING SOYBEAN LEAF RUST DISEASES Phakopsora pachyrhizi - Fenty Maimunah Simbolon; Sulaiman Ginting; S. Edy Sumantri; Mahyuddin Dalimunthe; Diski Andrian (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effectiveness of betel leaf extract (Piper betle) on the control of leaf rust disease Phakopsora pachyrhizi soybean plants. The research was carried out by UPT Palawija Crops, Department of Agriculture of the Province of North Sumatra Tanjung Selamat, Deli Serdang with an altitude of ±25 meters above sea level with a flat topography. The research method used a non- factorial randomized block design consisting of 4 treatments and 3 replications. The treatments tested were K0 = control, K1 = 0.25% extract concentration, K2 = 0.50% extract concentration, K3 = 0.75% extract concentration. Parameters observed were the percentage of infected plants, disease intensity and seed weight of 100 grains. The results showed that the pesticide of betel leaf (Piper betle) had a significant effect in controlling leaf rust disease Phakopsora pachyrhizi. The treatment was in K3 (0.75% extract) with a percentage of 2.1% being attacked. Compared to treatment K0 (Control) the percentage of infection was 6.9%, K1 (Extract 0.25%) percentage was attacked by 5.7%, and K2 (Extract 0.50%) the percentage was 3.2%. The conclusion of this study Betel leaf vegetable pesticides (Piper betle) are effective in controlling leaf rust disease Phakopsora pachyrhizi and can suppress the intensity of P. pachyrhizi attacks on soybean plants so that growth is not disturbed. Betel leaf extract (P. betle)) which was tested had a significant effect on controlling leaf rust (P. pachyrhizi) on soybeans (Glycine max. L) in K3 treatment with the percentage of infected plants being 2.1%.